2010
DOI: 10.5005/johcd-4-2-42
|View full text |Cite
|
Sign up to set email alerts
|

Adult Orthodontics Versus Adolescent Orthodontics: An Overview

Abstract: The scope of orthodontics has widened to include not only children and adolescents but also adults, thereby abolishing the upper age limit. With growing esthetic conscience among the society, a great number of young adults are seeking orthodontic treatment primarily for esthetic reasons. They undergo comprehensive orthodontic treatment involving major occlusal changes to get the utmost esthetically pleasing face. The older adults with poor dental conditions requiring perio-restorative treatment undergo adjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…Adult patients with some pre-existing periodontal disease are at a higher risk of developing periodontal problems [ 17 ]. Orthodontic treatment is not contraindicated in this group of patients if they are motivated to maintain good oral hygiene & the disease is kept under control throughout the duration of treatment [ 18 ].…”
Section: Attachment Lossmentioning
confidence: 99%
“…Adult patients with some pre-existing periodontal disease are at a higher risk of developing periodontal problems [ 17 ]. Orthodontic treatment is not contraindicated in this group of patients if they are motivated to maintain good oral hygiene & the disease is kept under control throughout the duration of treatment [ 18 ].…”
Section: Attachment Lossmentioning
confidence: 99%
“…29 Orthodontic uprighting of tipped teeth may also eliminate plaque-retentive areas and reduce periodontal pocket depths on mesial surfaces. [30][31][32] Second, occlusal conditions may have contributed to the lower prevalence of periodontitis in the orthodontic treatment group in this study. Traumatic occlusion has Figure 1.…”
Section: Discussionmentioning
confidence: 83%
“…Alveolar cleft reconstruction and accelerated orthodontic tooth movement are matters of concern in contemporary orthodontics [28,40]. However, few studies were found assessing application of PRF on orthodontics compared to other dentistry areas.…”
Section: Discussionmentioning
confidence: 99%